Feedback to managers : a guide to reviewing and selecting multirater instruments for leadership development. - Leslie, Jean Brittain (Center for Creative Leadership, 2013)
Feedback is a rare commodity in day-to-day organizational life, but it is a key to ongoing effectiveness. One popular vehicle for getting feedback from one's boss, peers, subordinates, and customers is the multiple-perspective or 360-degree-feedback instrument. Whether part of a management-development course or used alone, this kind of instrument can enhance self-awareness by highlighting a leader's strengths and areas in need of further development. Selecting the right instrument from among the dozens that are available can be difficult, however. This new edition of Feedback to Managers, the fourth, updates and expands the popular 1998 edition. It guides the selection process with an in-depth analysis of 32 publicly available instruments that relate self-view to the views of others on multiple management or leadership domains. Each of the instrument reports includes descriptive information, a look at the research behind the instrument, and descriptions of support materials.